2011
DOI: 10.1007/s00422-011-0425-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutual information and redundancy in spontaneous communication between cortical neurons

Abstract: An important question in neural information processing is how neurons cooperate to transmit information. To study this question, we resort to the concept of redundancy in the information transmitted by a group of neurons and, at the same time, we introduce a novel concept for measuring cooperation between pairs of neurons called relative mutual information (RMI). Specifically, we studied these two parameters for spike trains generated by neighboring neurons from the primary visual cortex in the awake, freely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Also, the results showed that, in our model, most of the neuronal architectures were highly redundant, most of the neurons in the higher performance configurations presented independent activity, and that increasing the number of neurons in a network with fixed number of assemblies increased the redundancy. All these findings resemble the results obtained in real cortical experiments, therefore a few remarks should be made: first, real neuronal ensembles are highly redundant, and that can be associated with resistance to error and natural mechanisms of probability distribution estimation (Barlow, 2001;Szczepanski et al, 2011); second, neuronal independence (as observed in our results) can be linked to code efficiency because the information capacity of individual neurons is not compromised by redundant scenarios (Schneidman et al, 2003); and third, there is still a lack of studies comparing the information flow dynamics due to neuronal interactions and due to single neurons alone -attesting the time-scales of the interactions as well as spurious effects such as averaging is still work in progress (Reich et al, 2001;Narayanan et al, 2005).…”
Section: B Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Also, the results showed that, in our model, most of the neuronal architectures were highly redundant, most of the neurons in the higher performance configurations presented independent activity, and that increasing the number of neurons in a network with fixed number of assemblies increased the redundancy. All these findings resemble the results obtained in real cortical experiments, therefore a few remarks should be made: first, real neuronal ensembles are highly redundant, and that can be associated with resistance to error and natural mechanisms of probability distribution estimation (Barlow, 2001;Szczepanski et al, 2011); second, neuronal independence (as observed in our results) can be linked to code efficiency because the information capacity of individual neurons is not compromised by redundant scenarios (Schneidman et al, 2003); and third, there is still a lack of studies comparing the information flow dynamics due to neuronal interactions and due to single neurons alone -attesting the time-scales of the interactions as well as spurious effects such as averaging is still work in progress (Reich et al, 2001;Narayanan et al, 2005).…”
Section: B Resultssupporting
confidence: 76%
“…The intuition that noisy scenarios are better tackled with redundant architectures is justified -there are works showing that cortical circuits, which operate in an intrinsically noisy environment, are highly redundant (Narayanan et al, 2005;Szczepanski et al, 2011). However, there is criticism regarding the interpretation of information theoretical measurements such as redundancy (Schneidman et al, 2003;Latham & Nirenberg, 2005), as well as findings showing predominantly synergistic or independent activity in neuronal circuits, instead of redundancy, depending on factors such as which area and which neurons are recorded or which kind of task is performed (Reich et al, 2001).…”
Section: B Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are mainly interested in studying how ET E between these variables vary as the task progresses, given that the agent continually engages with the object during the discrimination and orientation processes. For this purpose, a sliding window technique is used (Staniek & Lehnertz, 2008;Szczepanski et al, 2011), with a window size of 200 data points. Therefore, at every time step of the task, the ET E is estimated (according to Equations 5 and 6) considering the time series contained in that window.…”
Section: Transfer Entropymentioning
confidence: 99%
“…The question of how neurons interact has gained considerable attention over the years [1], [2]. Traditional methods emphasize the strength of pairwise connections, i.e.…”
Section: Introductionmentioning
confidence: 99%